Atlas of the environment - Geoffrey Lean (ABC-CLIO, 1994)
The book provides the most up-to-date report possible on the state of the world's environment. With over 200 full-color maps and diagrams, the book explains what is happening to our planet - including disappearing forests, acid rain, climate change, pollution, and desertification